Correlations between rail grease formulation and friction, wear and RCF of a wheel/rail tribological pair. (January 2021) - Biazon, L.; Ferrer, B.P.; Toro, A.; Cousseau, T.
Abstract: Twin disc tests were employed to assess rail grease formulation effect on friction, wear, and retentivity to propose guidelines for grease selection based on key aspects of grease formulation. Two commercial rail greases plus six in-house formulated greases with the same additive package and consistency, but different thickener types and base oil viscosities were evaluated. The results showed that: i) at low nominal lambda ratio, crack propagation and friction coefficient are highly dependent on thickener type - both increase for Calcium and decrease for Lithium; ii) at high nominal lambda ratio, friction and wear are controlled by the base oil viscosity; iii) retentivity is controlled by the base oil viscosity regardless of the nominal specific film thickness or thickener type. Graphical abstract: Image 1 Highlights: Calcium thickener is more likely to pass through the contact than Lithium thickener, enhancing its grease film thickness. In the thickener dominant region, films from Calcium greases present higher friction than Lithium grease. Crack propagation is higher with Calcium thickener than Lithium due to higher friction and surface deposition probability. Retentivity increases with viscosity, while the effect of thickener type is negligible.